Study of the transcriptomic profile in endothelial cells on regenerative vascular grafts under static and dynamic conditions (2021)
Among pathologies with the highest incidence worldwide, those associated with cardiovascular-type problems affect a large number of patients. Many of these conditions affect the patient's arterial system to the point that surgical interventions are necessary to replace them. Given this fact, the study of vascular grafts has presented great challenges derived from the issues present in the functionality of these replacements. Among the problems of greatest relevance for the functional acceptance of the grafts is the physiological alteration of cells and blood with the biomaterials of which the graft itself is composed. Although great strides have been made in the development of biomaterials to address the adjacent problem related to the functionality of the implantations, it is still not possible to obtain satisfactory results that allow us to allude to acceptable forecasts for vascular replacement. For this reason, it is necessary to understand the differences in processes at the molecular level between cell groups...